Persepsi Masyarakat Dalam Kegiatan Antropogenik Yang Berpengaruh Terhadap Kerentanan Das Hulu Percut - Jennifer Sri Pinta Pakpahan (Universitas Andi Djemma Palopo, 2022)
ABSTRACTÂ Anthropogenic danger is a danger that arises as a result of human actions or mistakes. Anthropogenic hazards can affect humans as well as wider ecosystems and various landforms. The influence of human activities on river ecosystems has encouraged the development of the concept of bioindicators to determine the health status of aquatic ecosystems. Percut river water quality is influenced by human activities that utilize the land around the river. The activities carried out by the community are for irrigation sources, pond irrigation, sand excavation and daily needs. Assessment of watershed vulnerability to anthropogenic activities using community perception approach. It is used because people's perceptions can directly build awareness and alertness in the face of danger and vulnerability. This study aims to determine the perception of society in anthropogenic activities in the upstream Percut watershed area and determine the relationship between the perception of the upstream Percut watershed to the behavior of anthropogenic activities that affect the vulnerability of watershed. This study uses survey methods. Data collection was done by: (a) Observation (observation), (b) structured and free interviews (questionnaires), and (c) secondary Data that support the research and the data were analyzed using Spearman rank correlation test. The results showed that the level of public perception in anthropogenic activities that affect the vulnerability of watershed is included in the category of moderate. Upstream communities assume that if the river is damaged, it will cause damage to the downstream, which will then affect the needs of the community directly. The perception and behavior of upstream peoples towards anthropogenic activities falls into the category of moderate. That means that there is no relationship between perception and behavior in the upstream Percut watershed quality.Â Â Keywords : Upstream Percut Watershed, Perception, Behavior, Anthropogenic